Pengaruh Struktur Modal, Efisiensi dan Kemampuan Laba Terhadap Nilai Perusahaan Sektor Aneka Industri yang Terdaftar di BEI Periode 2014-2018 - Cynthia Devira; Sarjono Sahar (UNIVERSITAS KALBIS, 2022)
This study aims to examine the effect of capital structure, efficiency, profitability and earning per share on firm value. The population in this study is misscellaneous industry sector listed on Indonesia Stock Exchange in the period 2014-2018. The determination of the sample used a purposive sampling method so that there are 16 that are in accirdance with the research criteria selected as the sample of this study. The data analysis method used in this study is multiple regression analysis using SPSS version 25. The result of this study indicate that partially capital structure, profitability as measured by net profit margin (NPM) has a significant positive effect on firm value and earning per share (EPS) has a significant negative effect on firm value. While efficiency does not affect on firm value. Simultaneous results show that capital structure, efficiency, profitability and earning per share affect to firm value.